Quantum dot-based light-emitting micro device and transient emulsion method sequential preparation method thereof
By assembling quantum dot primitives using a transient emulsion method in the hole template, the leakage current problem caused by direct contact between the hole transport layer and the electron transport layer in the prior art is solved, and the high resolution and performance requirements of Micro-QLED are achieved, reducing manufacturing costs.
Patent Information
- Application Number
- CN202411509090.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-28
- Publication Date
- 2025-02-28
- Estimated Expiration
- 2044-10-28
AI Technical Summary
In the existing quantum dot micro-domain preparation processes such as inkjet printing, transfer printing, and lithography, the hole transport layer and the electron transport layer are directly in contact, causing leakage current, affecting the device's luminous efficiency. At the same time, it is difficult to obtain uniform and dense quantum dot films in inkjet printing, which cannot meet the new process requirements of Micro-QLED.
The large-area, precise quantification and positioning of quantum dot primitives are used to realize the assembly sequence of large-area, precise quantification and positioning of quantum dots in the pore template. Through the assembly of PEDOT:PSS and CdSe/ZnS aqueous quantum dots, a discontinuous film layer is formed, and spin-coated on the ZnO layer to form a continuous layer, and finally vacuum evaporation is used to form an Ag electrode.
It reduces the leakage current of the device, improves the luminous efficiency, realizes the miniaturization of pixel units, meets the high resolution and performance requirements of Micro-QLED, and reduces manufacturing costs.
Smart Images

Figure CN119546145A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of quantum dot light-emitting devices, and in particular to a quantum dot-based light-emitting micro-device and a transient emulsion method for preparing the same. Background Art
[0002] The contemporary display industry has entered a hot stage of "renewal and replacement", and various display technology innovations have emerged, such as the constantly improved backlight liquid crystal display (LCD), organic self-light-emitting diode (OLED) display, quantum dot self-light-emitting diode (QLED) display, micro-semiconductor self-luminous Micro-LED display and laser LD display, presenting a multi-legged business landscape.
[0003] For Micro-QLED, the new process requirement is to improve the performance of the device on the basis of achieving high resolution of the device. Generally speaking, the quantum dots in QLED cannot be processed by traditional evaporation process because they are easily affected by temperature and humidity. Relatively mild extensive processes such as spin coating, dip coating, and brush coating are usually used. In order to achieve accurate quantification of its pixel points, inkjet printing is required. Compared with spin coating, inkjet printing technology reduces material waste and can achieve patterned and full-color printing, which is suitable for the preparation of large-area devices. However, the ink droplet size in inkjet printing is generally in the order of hundreds of microns, and high-resolution pattern printing cannot be achieved. And due to the coffee ring effect, it is difficult to obtain a uniform and dense quantum dot film. Therefore, inkjet printing cannot meet the new process requirements proposed by Micro-QLED. In addition, for the existing quantum dot micro-device preparation processes such as inkjet printing, transfer printing, and photolithography, most of these processes are patterning or miniaturization of the quantum dot light-emitting layer, and the remaining functional layers are spin-coated. In such a process, the hole transport layer and the electron transport layer are in direct contact, resulting in serious leakage current, which in turn affects the luminous efficiency of the device. Therefore, new processes are needed to improve this phenomenon. Summary of the invention
[0004] In view of the above shortcomings in the prior art, the present invention provides a method for preparing transient emulsion structures for quantum dot-based light-emitting microdevices, which utilizes the confinement effect of the hole template and the transient emulsion method to achieve large-area, precise quantitative and positioned assembly structures of nanostructured primitives in the holes.
[0005] To achieve the above object, the present invention adopts the following technical solution: a method for preparing a transient emulsion structure for quantum dot-based light-emitting microdevices, comprising the following steps:
[0006] Step A, taking a template with a microwell array, wherein the wall of the array wells in the template is made of a hydrophobic material and the bottom of the wells is made of a conductive hydrophilic material, dripping n-butanol on the surface where the array well openings are located until the array wells are completely filled, standing until the array wells are fully infiltrated, and removing excess n-butanol outside the array wells;
[0007] Step B, dripping PEDOT:PSS solution on the surface where the array hole openings are located, and standing for a period of time, the n-butanol and PEDOT:PSS solution are dissolved and fill the array holes;
[0008] Step C, removing excess n-butanol and PEDOT:PSS solution outside the array holes, then standing to dry, and assembling to form a discontinuous PEDOT:PSS film layer in the array holes;
[0009] Step D, adding n-butanol dropwise into the array holes where the PEDOT:PSS film layer is formed, and after the array holes are allowed to stand until they are fully infiltrated, removing excess n-butanol outside the array holes;
[0010] Step E, adding CdSe / ZnS water-phase quantum dots dropwise into n-butanol in the array holes, and standing until the CdSe / ZnS water-phase quantum dots and n-butanol are dissolved and fill the array holes;
[0011] Step F, removing excess n-butanol and CdSe / ZnS aqueous quantum dot solution, then standing to dry, and assembling on the surface of the PEDOT:PSS film layer in the array holes to form a discontinuous aqueous quantum dot film layer;
[0012] Step G, dripping ZnO ethanol solution on the surface where the array hole openings are located, spin coating, and drying to form a continuous ZnO layer;
[0013] Step H: using a vacuum evaporator to form a Ag electrode on the surface of the ZnO layer by vacuum evaporation, and then encapsulating to obtain a quantum dot-based light-emitting micro-device.
[0014] As a further improvement of the transient emulsion structure preparation method for quantum dot-based light-emitting microdevices:
[0015] Preferably, before adding n-butanol to the surface where the array hole openings are located in step A, the template is first placed in an oxygen plasma cleaning machine for treatment for 60s-300s.
[0016] Preferably, the shape of the micropores on the template in step A is one of square, circle, triangle, and diamond; the opening area of a single pore is 0.25 μm 2 -6400μm 2 , diameter is 500nm-80μm, the closest spacing of the holes is 5μm-80μm, and the depth of the holes is 5μm-40μm.
[0017] Preferably, the concentration of n-butanol is 90 wt%-99.9 wt%. After n-butanol is added dropwise in steps A and D, the mixture is left standing in air until the array holes are fully wetted, and the standing time is 20 s-600 s.
[0018] Preferably, in the PEDOT:PSS solution described in step B, the model of the PEDOT:PSS solution is 4083, the concentration is 1.3-1.7wt%, and the PEDOT:PSS solution is added dropwise and then allowed to stand for 20s-600s; the standing drying time in steps C and F is 1h-12h, and the temperature is 40°C-300°C.
[0019] Preferably, in step E, after the CdSe / ZnS aqueous quantum dot solution is added dropwise, the solution is left to stand for 20s-600s, wherein the ligand of the CdSe / ZnS aqueous quantum dot solution is MPA mercaptopropionic acid, the wavelength is 625±10nm, and the concentration is 1nmol / mL-20nmol / mL.
[0020] Preferably, the concentration of ZnO in the ethanol solution of ZnO in step G is 20-1000 mg / ml.
[0021] Preferably, the spin coating in step G is performed on a glue spreader, the speed of the glue spreader is set to 2000rpm-7000rpm, and the time is 30s-100s; the drying in step G is performed in a glue baking machine, the temperature of the glue baking machine is set to 40℃-150℃, and the baking time is 20min-50min.
[0022] Preferably, the thickness of the Ag electrode in step H is 50nm-200nm.
[0023] The second object of the present invention is to provide a quantum dot-based light-emitting microdevice prepared by any one of the transient emulsion sequence preparation methods for quantum dot-based light-emitting microdevices.
[0024] Compared with the prior art, the present invention has the following beneficial effects:
[0025] 1) For the existing preparation processes of quantum dot micro devices such as inkjet printing, transfer printing, and photolithography, most of these processes are to pattern or miniaturize the quantum dot light-emitting layer, and the remaining functional layers are all spin-coated. Because the hole transport layer will be in direct contact with the electron transport layer in these preparation processes, leakage current will occur during the operation of the device, thereby affecting the performance of the device. The present invention realizes device miniaturization by introducing each functional layer into the photoresist hole array, so that it can be assembled only in the micropores. And it is isolated by photoresist, which will not cause poor contact between the devices. Therefore, there will be no phenomenon of direct contact between the hole transport layer and the electron transport layer, thereby reducing the leakage current of the device and achieving the effect of improving the performance of the device.
[0026] 2) Due to the coffee ring effect, it is difficult to obtain a uniform and dense quantum dot film using inkjet printing technology. The present invention utilizes the intrinsic advantage of the transient emulsion system that it is easy to confine emulsify, and can obtain micron-level or even hundreds of nanometer-level emulsion droplets in the template micropores. The present invention uses a template composed of a hydrophobic material (such as photoresist) and a conductive hydrophilic material (ITO) with an orderly arranged and uniformly sized micropore array, so that the bottom of the hole is hydrophilic and the side wall is hydrophobic, so that the water phase is spread flat on the bottom, making the interface flat. The PEDOT:PSS solution used is a poly (3,4-ethylenedioxythiophene) polystyrene sulfonate solution, which is a conductive polymer and can be dissolved in n-butanol and filled in the array holes. CdSe / ZnS aqueous phase quantum dots are CdSe / ZnS aqueous phase quantum dots with a core-shell structure, and the ligand is mercaptopropionic acid MPA, with a wavelength of 625±10nm. When the diameter of quantum dots is at the nanometer level, rapid assembly of microspheres can be achieved, and when the diameter of colloidal spheres is at the micrometer level, uniform distribution of spheres can be achieved, thereby forming a microplanar array in the array micropores of the micropore array substrate, achieving the purpose of miniaturization of the structure of each functional layer.
[0027] 3) The present invention utilizes a new transient emulsion system with two phases partially miscible, and provides a transient emulsion method for quantum dot-based light-emitting microdevices. The so-called "transient" describes a short process in which the emulsified droplets diffuse rapidly and are exhausted in a partially miscible emulsion system. For example, the existence time of micron-sized water droplets in the n-butanol phase is only on the order of seconds (proportional to the droplet size). Further, according to the Young-Laplace equation, it can be seen that this type of transient emulsion droplets is in a completely miscible state due to the dynamic diffusion of the two phases at the interface, and its surface tension can be ignored. Therefore, micron-level emulsification can be achieved without strong fluid shear disturbance, and any small droplet size can be achieved in theory. Compared with the hundreds of microns of inkjet printing, the present invention has a great degree of improvement. The present invention can achieve the miniaturization of pixel units by introducing the transient emulsion method into the system and preparing a complete device in a microporous template, thereby meeting the new micro-process requirements proposed by Micro-QLED.
[0028] 4) The preparation process of this technology is simple and versatile, and does not require precise and expensive instruments. It can greatly reduce the cost and production time of quantum dot microdevices, greatly improving production efficiency. It provides a good confinement effect for the assembly of subsequent structures, ensures the orderly arrangement of the assembled structure and the uniformity of size, and greatly weakens the randomness of traditional self-assembly strategies.
[0029] 5) The present invention is based on a water-n-butanol transient emulsion system, which can not only simply adjust the concentration of the substance in the aqueous solution to adjust the thickness of the final assembled functional layer, thereby achieving the purpose of improving device performance, but also can achieve the purpose of improving the quality of each functional layer film by adjusting the difference in hydrophilicity and hydrophobicity. In this process, only simple concentration adjustment and hydrophilicity adjustment are required, and the process is simple and convenient. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings required for use in the description of the embodiments will be briefly introduced below. Obviously, the accompanying drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other accompanying drawings can be obtained based on these accompanying drawings without paying creative work.
[0031] Figure 1 This is an optical microscope photograph obtained by observing the prepared hemispherical PEDOT:PSS solution using a Zeiss microscope in Example 1 of the present invention. Figure 1 a in the figure corresponds to the PEDOT:PSS transient emulsion assembly result when the concentration of PEDOT:PSS solution is 1.4wt%. Figure 1 b corresponds to the PEDOT:PSS transient emulsion assembly result when the concentration of PEDOT:PSS solution is 0.7wt%. Figure 1 Figure c corresponds to the PEDOT:PSS transient emulsion assembly result when the concentration of the PEDOT:PSS solution is 0.35wt%.
[0032] Figure 2 This is a picture obtained by analyzing the prepared hemispherical functional layer PEDOT:PSS solution using an atomic force microscope (AFM) in Example 1 of the present invention. Figure 2 a in the figure corresponds to the PEDOT:PSS transient emulsion assembly result when the concentration of PEDOT:PSS solution is 1.4wt%. Figure 2 b corresponds to the PEDOT:PSS transient emulsion assembly result when the concentration of PEDOT:PSS solution is 0.7wt%. Figure 2 Figure c corresponds to the PEDOT:PSS transient emulsion assembly result when the concentration of the PEDOT:PSS solution is 0.35wt%.
[0033] Figure 3 This is an optical microscope image obtained by observing the prepared layered PEDOT:PSS solution using a Zeiss microscope in Example 2 of the present invention.
[0034] Figure 4It is a schematic flow chart of the method for preparing quantum dot-based light-emitting microdevices by using transient emulsion sequencing process + spin coating process in comparative examples 1 and 2 of the present invention.
[0035] Figure 5 This is an optical microscope picture obtained by observing the electroluminescence of the complete QLED device prepared in Comparative Example 1 of the present invention using a Zeiss microscope.
[0036] Figure 6 This is an optical microscope picture obtained by observing the electroluminescence of the complete QLED device prepared in Comparative Example 2 of the present invention using a Zeiss microscope.
[0037] Figure 7 This is a performance comparison chart of the complete QLED devices prepared in Comparative Example 1 and Comparative Example 2 of the present invention.
[0038] in Figure 7 a in the figure corresponds to the leakage current performance of the device. Figure 7 b in the figure corresponds to the brightness performance of the device. Figure 7 The c in the middle corresponds to the external quantum efficiency (EQE) of the device.
[0039] Figure 8 Schematic diagram of the process for preparing quantum dot-based light-emitting microdevices using two transient emulsion sequencing processes in Example 3. DETAILED DESCRIPTION
[0040] The following is a clear and complete description of the technical solutions in the embodiments of the present invention in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the protection scope of the present invention.
[0041] First, the domestic SU8-2050 photoresist, domestic developer (universal type), poly(3,4-ethylenedioxythiophene) polystyrene sulfonate (PEDOT:PSS solution, model 4083, concentration 1.3-1.7wt%), poly[(9,9-dioctylfluorenyl-2,7-diyl)-co-(4,4'-(N-(p-butylphenyl))diphenylamine)] (TFB), CdSe / ZnS oil phase quantum dots (solution: n-octane, concentration: 10mg / mL) CdSe / ZnS water phase quantum dots (ligand mercaptopropionic acid MPA, wavelength 625±10nm, concentration 10nmol / mL), ZnO nanoparticles (concentration 30mg / ml, solvent ethanol), n-butanol (concentration 90wt%-99.9wt%), ethanol solution, acetone solution, chlorobenzene solution are purchased from the market.
[0042] Example 1
[0043] This embodiment provides a method for preparing an orderly arranged PEDOT:PSS solution layered structure array, which specifically includes the following steps:
[0044] S1. Take a template with a micropore array, in which the pore walls of the array pores are made of a hydrophobic material (photoresist), the pore bottoms are made of a conductive hydrophilic material (ITO), the pore openings are square in shape, the opening size is 40 μm×40 μm, the closest spacing between adjacent pores is 20 μm, and the pore depth is 1 μm;
[0045] Add 6 μl of n-butanol on the surface where the array wells are located until the array wells are completely filled. After the array wells are allowed to stand in air until they are fully infiltrated, remove the excess n-butanol outside the array wells.
[0046] S2, add 5 μl of PEDOT:PSS solution (concentration of 1.4 wt%) to the surface where the array holes are located, and let it stand in air for 20 seconds, so that n-butanol and PEDOT:PSS solution dissolve and fill the array holes;
[0047] S3. Remove excess n-butanol and PEDOT:PSS solution outside the array holes, then place in an oven at 75°C for 1 hour to dry, and assemble in a single hole in the array holes to form a discontinuous hemispherical PEDOT:PSS film layer.
[0048] Referring to the above steps, the concentrations of the PEDOT:PSS solution (model 4083) in step S2 were changed to 0.7 wt % and 0.35 wt %, respectively, and hemispherical PEDOT:PSS membrane layers were assembled in individual holes in the array holes.
[0049] Figure 1 This is an optical microscope photograph obtained by observing the prepared hemispherical PEDOT:PSS solution using a Zeiss microscope in Example 1 of the present invention. Figure 1 a in the figure corresponds to the PEDOT:PSS transient emulsion assembly result when the concentration of PEDOT:PSS solution is 1.4wt%. Figure 1 b corresponds to the PEDOT:PSS transient emulsion assembly result when the concentration of PEDOT:PSS solution is 0.7wt%. Figure 1 The c in the figure corresponds to the PEDOT:PSS transient emulsion assembly result when the concentration of the PEDOT:PSS solution is 0.35wt%. Figure 1 It can be seen that an orderly arranged PEDOT:PSS solution hemispherical structure array is prepared through this embodiment, and the height and size of the hemispherical structure can be controlled by adjusting the concentration of the PEDOT:PSS solution.
[0050] Figure 2 This is a picture obtained by analyzing the hemispherical functional layer PEDOT:PSS solution obtained in step S3 using an atomic force microscope (AFM) in Example 1 of the present invention. Figure 2 a in the figure corresponds to the PEDOT:PSS transient emulsion assembly result when the concentration of PEDOT:PSS solution is 1.4wt%. Figure 2 b corresponds to the PEDOT:PSS transient emulsion assembly result when the concentration of PEDOT:PSS solution is 0.7wt%. Figure 2 The c in the figure corresponds to the PEDOT:PSS transient emulsion assembly result when the concentration of the PEDOT:PSS solution is 0.35wt%. Figure 2 It can be seen that an orderly arranged PEDOT:PSS solution hemispherical structure array is prepared through this embodiment, and the height and size of the hemispherical structure can be controlled by adjusting the concentration of the PEDOT:PSS solution.
[0051] Example 2
[0052] This embodiment provides a method for preparing an ordered PEDOT:PSS solution layered structure array, and the specific steps are referred to Example 1, except that the template of the microwell array in step S1 is first placed in an oxygen plasma cleaner for 60 seconds before 6 μl of n-butanol is added. Finally, a discontinuous layered PEDOT:PSS film layer is assembled in a single hole in the array hole.
[0053] Figure 3 The optical microscope image obtained by observing the layered PEDOT:PSS solution prepared in Example 2 of the present invention using a Zeiss microscope. Figure 3 As shown, the above embodiment prepared an orderly arranged layered PEDOT:PSS solution structure array.
[0054] Comparative Example 1
[0055] This embodiment provides a method for preparing a quantum dot-based light-emitting micro-device using a transient emulsion sequencing process + a spin coating process. The preparation process is as follows: Figure 4 As shown, the specific steps include:
[0056] S1. Take a template with a micropore array, in which the pore walls of the array pores are made of a hydrophobic material (photoresist), the pore bottoms are made of a conductive hydrophilic material (ITO), the pore openings are square in shape, the opening size is 40 μm×40 μm, the closest spacing between adjacent pores is 20 μm, and the pore depth is 1 μm;
[0057] Add 6 μl of n-butanol on the surface where the array wells are located until the array wells are completely filled. After the array wells are allowed to stand in air until they are fully infiltrated, remove the excess n-butanol outside the array wells.
[0058] S2, add 5 μl of PEDOT:PSS solution (model 4083) (concentration of 1.4 wt%) to the surface where the array hole opening is located, and let it stand in air for 20 seconds to allow the two solutions to dissolve and fill the array holes;
[0059] S3, removing the excess n-butanol and PEDOT:PSS solution outside the array holes, then placing in an oven at 75°C for 1 hour to dry, and assembling in a single hole in the array hole to form a discontinuous hemispherical PEDOT:PSS film layer (as a hole injection layer);
[0060] S4, prepare TFB solution (concentration of 7 mg / mL, chlorobenzene solution); place the template assembled with PEDOT:PSS film layer on a glue machine, add TFB solution dropwise into the array holes assembled with PEDOT:PSS film layer, set the rotation speed to 3000 rpm, and the spin coating time to 40 s; then place the template in a glue baking machine at a temperature of 120°C for 20 min, and dry to obtain a continuous TFB layer (as a hole transport layer);
[0061] S5, placing the prepared TFB layer template on a glue spreader, dripping the oil phase quantum dot solution onto the TFB layer, setting the rotation speed to 2000 rpm, and the spin coating time to 30 seconds; then placing the template in a glue baking machine, the temperature is 80°C, the time is 20 minutes, and drying to obtain a continuous oil phase quantum dot layer (as a quantum dot light-emitting layer);
[0062] S6, placing the template of the prepared oil phase quantum dot layer on a glue machine, adding ZnO ethanol solution (ZnO concentration is 3 mg / ml) dropwise onto the oil phase quantum dot layer, setting the rotation speed to 2000 rpm, the spin coating time to 30 s, and then placing the template in a glue baking machine at a temperature of 80° C. for 20 min, and drying to obtain a continuous ZnO layer (as an electron injection layer);
[0063] S7. Use a vacuum evaporator to vacuum evaporate and form an Ag electrode with a thickness of 100 nm on the surface of the ZnO layer, and then package it to obtain a complete QLED device.
[0064] Comparative Example 2
[0065] This embodiment provides a method for preparing a quantum dot-based light-emitting micro-device using a transient emulsion sequencing process + a spin coating process. The preparation process is as follows: Figure 4As shown, the specific steps refer to comparative example 1, except that the template of the microwell array in step S1 is first placed in an oxygen plasma cleaner for 60 seconds before 6 μl of n-butanol is added. Step S3 assembles a layered PEDOT:PSS film layer in a single hole in the array hole. Finally, a complete QLED device is obtained.
[0066] Figure 4 The figure is a flow chart of the transient emulsion method for preparing quantum dot-based light-emitting microdevices in comparative examples 1 and 2 of the present invention. The specific process is described as follows: the first step is to wet the template with n-butanol; the second step is to drop the PEDOT:PSS solution into the hole, assemble it in nanoseconds, and assemble it in the array hole to form a PEDOT:PSS film layer (as a hole injection layer) after drying; then the hole transport layer, quantum dot light-emitting layer, and electron injection layer are spin-coated in sequence, and finally the Ag electrode is plated to obtain a complete QLED device.
[0067] Figure 5 This is an electroluminescence microscopic image of the complete QLED device prepared in Comparative Example 1 of the present invention. Figure 6 This is an electroluminescent microscopic image of a complete QLED device prepared in Comparative Example 2 of the present invention. Figure 5 It can be seen that when a hemispherical PEDOT:PSS film layer is assembled in a single hole in the array hole, it is not conducive to the uniform light emission of the device and will cause the center of the device to fail to light up. Figure 6 It can be seen that when a layered PEDOT:PSS film layer is assembled in a single hole in the array hole, uniform light emission of the device can be achieved and the brightness of the device is also significantly improved.
[0068] Figure 7 The performance comparison diagram of the complete QLED device prepared in Comparative Example 1 and Comparative Example 2 of the present invention is shown in FIG. The device is placed in the test platform, and the current meter is turned on for measurement to obtain the performance data. Figure 7 a in the figure corresponds to the leakage current performance of the device. Figure 7 b in the figure corresponds to the brightness performance of the device. Figure 7 Where c corresponds to the external quantum efficiency (EQE) of the device. Figure 7 It can be seen that, compared with the PEDOT assembled into a hemispherical structure in Comparative Example 1, the PEDOT:PSS solution assembled into a layered structure in Comparative Example 2 can obtain better performance, such as a significant decrease in leakage current and improved brightness.
[0069] Example 3
[0070] This embodiment provides a method for preparing a quantum dot-based light-emitting micro-device by two transient emulsion sequencing processes. The preparation process is as follows: Figure 8 As shown, the following steps are included:
[0071] S1. Take a template with a micropore array, in which the pore walls of the array pores are made of a hydrophobic material (photoresist), the pore bottoms are made of a conductive hydrophilic material (ITO), the pore openings are square in shape, the opening size is 40 μm×40 μm, the closest spacing between adjacent pores is 20 μm, and the pore depth is 1 μm;
[0072] Add 6 μl of n-butanol on the surface where the array wells are located until the array wells are completely filled. After the array wells are allowed to stand in air until they are fully infiltrated, remove the excess n-butanol outside the array wells.
[0073] S2, add 5 μl of PEDOT:PSS solution (model 4083) (concentration of 1.4 wt%) to the surface where the array hole opening is located, and let it stand in air for 20 seconds to allow the two solutions to dissolve and fill the array holes;
[0074] S3, removing excess n-butanol and PEDOT:PSS solution outside the array holes, then placing in an oven at 75°C for 1 hour to dry, and assembling in the array holes to form a discontinuous PEDOT:PSS film layer (as a hole injection layer);
[0075] S4, adding n-butanol dropwise into the array holes where the PEDOT:PSS film layer is formed, and after the array holes are allowed to stand in an air atmosphere until the array holes are fully infiltrated, removing excess n-butanol outside the array holes;
[0076] S5, add 5 μl of CdSe / ZnS aqueous quantum dots (concentration: 10 nmol / ml, solvent: deionized water, luminescence wavelength: 625 nm, ligand: MPA) dropwise into the n-butanol in the array wells, and let stand in air for 20 seconds, so that the two solutions dissolve and fill the inside of the array wells;
[0077] S6, removing excess n-butanol and CdSe / ZnS aqueous quantum dots, and then placing in an oven at 75°C to dry for 0.5 h, assembling on the surface of the PEDOT:PSS film layer in the array holes to form a discontinuous aqueous quantum dot film layer (as a quantum dot light-emitting layer);
[0078] S7, placing the template of the prepared water phase quantum dot layer on a glue machine, adding ZnO ethanol solution (ZnO concentration is 3 mg / ml) dropwise onto the oil phase quantum dot layer, setting the rotation speed to 2000 rpm, the spin coating time to 30 s, and then placing the template in a glue baking machine at a temperature of 80° C. for 20 min, and drying to obtain a continuous ZnO layer (as an electron injection layer);
[0079] S8. Use a vacuum evaporator to vacuum evaporate and form a Ag electrode with a thickness of 100 nm on the surface of the ZnO layer, and then package it to obtain a quantum dot-based light-emitting microdevice.
[0080] Example 4
[0081] This embodiment provides a method for preparing a quantum dot-based light-emitting micro-device by two transient emulsion sequencing processes. The preparation process is as follows: Figure 8 As shown, the specific steps refer to Example 3, except that the template of the microwell array in step S1 is first placed in an oxygen plasma cleaner for 60 seconds before adding 6 μl of n-butanol. Step S3 assembles a layered PEDOT:PSS film layer in a single hole in the array hole. Finally, a quantum dot-based light-emitting microdevice is obtained.
[0082] The electroluminescent microscopic images of the quantum dot-based light-emitting microdevices prepared in Example 3 and Example 4 were collected, and the luminescent performance of the devices was tested. The test results confirmed that the present application utilized the confinement effect of the hole template and the transient emulsion method, and achieved large-area, precise quantitative and positioned assembly sequence of nanostructure elements in the hole through two transient emulsion method sequences. The quantum dot-based light-emitting microdevices prepared by the present invention will not have the phenomenon of direct contact between the hole transport layer and the electron transport layer, thereby reducing the leakage current of the device, achieving the effect of improving the performance of the device, and having excellent luminous efficiency. Compared with the existing inkjet printing, the embodiments of the present invention sequence the quantum dot elements in a specific manner, and directly construct a micron-scale self-luminous pixel chip on the substrate, without the need for complex micro-nano processing and mass transfer, thereby reducing manufacturing costs.
[0083] The above is only a preferred specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily thought of by any technician familiar with the field of the present invention within the technical scope disclosed in the present invention should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope of the claims.
Claims
1. A method for preparing a transient emulsion structure for quantum dot-based light-emitting microdevices, characterized in that: The following steps are involved: Step A, taking a template with a microwell array, wherein the wall of the array wells in the template is made of a hydrophobic material and the bottom of the wells is made of a conductive hydrophilic material, dripping n-butanol on the surface where the array well openings are located until the array wells are completely filled, standing until the array wells are fully infiltrated, and removing excess n-butanol outside the array wells; Step B, dripping PEDOT:PSS solution on the surface where the array hole openings are located, and standing for a period of time, the n-butanol and PEDOT:PSS solution are dissolved and fill the array holes; Step C, removing excess n-butanol and PEDOT:PSS solution outside the array holes, then standing to dry, and assembling to form a discontinuous PEDOT:PSS film layer in the array holes; Step D, adding n-butanol dropwise into the array holes where the PEDOT:PSS film layer is formed, and after the array holes are allowed to stand until they are fully infiltrated, removing excess n-butanol outside the array holes; Step E, adding CdSe / ZnS water-phase quantum dots dropwise into n-butanol in the array holes, and standing until the CdSe / ZnS water-phase quantum dots and n-butanol are dissolved and fill the array holes; Step F, removing excess n-butanol and CdSe / ZnS aqueous quantum dot solution, then standing to dry, and assembling on the surface of the PEDOT:PSS film layer in the array holes to form a discontinuous aqueous quantum dot film layer; Step G, dripping ZnO ethanol solution on the surface where the array hole openings are located, spin coating, and drying to form a continuous ZnO layer; Step H: using a vacuum evaporator to form a Ag electrode on the surface of the ZnO layer by vacuum evaporation, and then encapsulating to obtain a quantum dot-based light-emitting micro-device.
2. The method for preparing a transient emulsion structure for quantum dot-based light-emitting microdevices according to claim 1, characterized in that: Before adding n-butanol to the surface where the array hole openings are located in step A, the template is first placed in an oxygen plasma cleaning machine for treatment for 60s-300s.
3. The method for preparing a transient emulsion structure for a quantum dot-based light-emitting microdevice according to claim 1, characterized in that: The shape of the micropores on the template in step A is one of square, circle, triangle, and diamond; the opening area of a single pore is 0.25 μm 2 -6400μm 2 , diameter is 500nm-80μm, the closest spacing of the holes is 5μm-80μm, and the depth of the holes is 5μm-40μm.
4. The method for preparing a transient emulsion structure for a quantum dot-based light-emitting microdevice according to claim 1, characterized in that: The concentration of n-butanol is 90 wt%-99.9 wt%. After n-butanol is added dropwise in steps A and D, the mixture is left to stand in air until the array holes are fully wetted. The standing time is 20 s-600 s.
5. The method for preparing a transient emulsion structure for quantum dot-based light-emitting microdevices according to claim 1, characterized in that: In the PEDOT:PSS solution described in step B, the model of the PEDOT:PSS solution is 4083, the concentration is 1.3-1.7wt%, and the PEDOT:PSS solution is added dropwise and then allowed to stand for 20s-600s; in steps C and F, the standing and drying time is 1h-12h, and the temperature is 40°C-300°C.
6. The method for preparing a transient emulsion structure for quantum dot-based light-emitting microdevices according to claim 1, characterized in that: In step E, after the CdSe / ZnS aqueous quantum dot solution is added dropwise, the solution is allowed to stand for 20s-600s. The ligand of the CdSe / ZnS aqueous quantum dot solution is MPA mercaptopropionic acid, with a wavelength of 625±10nm and a concentration of 1nmol / mL-20nmol / mL.
7. The method for preparing a transient emulsion structure for quantum dot-based light-emitting microdevices according to claim 1, characterized in that: The concentration of ZnO in the ethanol solution of ZnO in step G is 20-1000 mg / ml.
8. The method for preparing a transient emulsion structure for quantum dot-based light-emitting microdevices according to claim 1, characterized in that: The spin coating in step G is performed on a glue spreader, the speed of the glue spreader is set to 2000rpm-7000rpm, and the time is 30s-100s; the drying in step G is performed in a glue baking machine, the temperature of the glue baking machine is set to 40℃-150℃, and the glue baking time is 20min-50min.
9. The method for preparing a transient emulsion structure for quantum dot-based light-emitting microdevices according to claim 1, characterized in that: The thickness of the Ag electrode in step H is 50nm-200nm.
10. A quantum dot-based light-emitting microdevice made by the transient emulsion sequence preparation method for quantum dot-based light-emitting microdevices as described in any one of claims 1 to 9.
Citation Information
Patent Citations
Orderly-arranged island-shaped heterostructure array and preparation method thereof
CN117624697A
Cross-interface deep hole array neural electrode capable of storing conductive polymer and preparation method
CN118452933A
Method for regulating and controlling confinement space by using external pressure and application of method in construction of three-dimensional micro-nano structure
CN118723914A
Transparent electrode with asymmetric light transmission and method of its manufacturing
RU2710481C1
Downward etching method for manufacturing perovskite micro-nano structure
WO2021195858A1